Factors that affect employee motivation towards the retail industry in Malaysia - Loo, Kai Liang; Lee, Jun Han; Tan, Hong Liang; Tan, Kean Hong (2023)
The retail industry has played a major role in Malaysia, as it has been one of the most significant contributors to the country’s gross domestic product (GDP) for decades. However, there is a lack of motivation among employees in the retail industry, and a high turnover rate of employees in Malaysia. The main objective of this research project is to examine the factors that affect employee motivation towards the retail industry in Malaysia which are salary, job security, co-worker relationship, employee recognition, competence, and employee training. Our research project is based on ERG theory to identify the factors that may affect the employee motivation. Then, pilot study, pre-test, reliability test, and validity test have been conducted before conducting the main study. A total of 390 responses were collected from the large-scale retail stores located in Perak, Penang and Terengganu. Most of the respondents are Malay female employees who are 21 to 29 years old, working for 6 to 9 years and mostly are SPM holders. To analyse the collected data, we applied SPSS Version 26 to run the data. Also, to test whether the factors have positively significant impact on employee motivation in retail industry, the multiple linear regression analysis was carried out. After analysing, the result showed that employee training and employee recognition have positively but insignificant impact on employee motivation, while salary, job security, co-worker relationship and competence have positively significant impact on employee motivation in the retail industry. Competence is the predictor variable that contributes the most to the variation of the dependent variable, following is job security, third is salary, fourth is co-worker relationship, fifth is employee training, and the lowest contribution is employee recognition. Furthermore, this research provides the implication for the manager to understand the factors that affect employee motivation in the retail industry in Malaysia. Also, some limitations and recommendations for the research have been highlighted to let the future researcher make the improvement.